2020
DOI: 10.31234/osf.io/frcks
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is the Myth of Left-Wing Authoritarianism Itself a Myth?

Abstract: Is left-wing authoritarianism (LWA) closer to a myth or a reality? Twelve studies test the empirical existence and theoretical relevance of LWA. Study 1 reveals that both conservative and liberal Americans identify a large number of left-wing authoritarians in their lives. In Study 2, participants explicitly rate items from a recently-developed LWA measure as valid measurements of authoritarianism. Studies 3-11 show that persons who score high on this same LWA scale possess the traits associated with models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 70 publications
(166 reference statements)
0
20
0
Order By: Relevance
“…Historically, many researchers have argued for the possibility of left-wing authoritarianism (e.g., Eysenck, 1954;Mullen et al, 2003;Ray, 1983;Rokeach, 1960;Shils, 1954), and burgeoning evidence spanning multiple nations and three continents validates many of these conceptual arguments Conway & McFarland, 2019;Conway et al, in press;Costello et al, 2020a;Conway et al, 2020b;De Regt, Mortelmans, & Smits, 2011;Fasce & Avendaño, 2020;Federico et al, 2017;McFarland et al, 1992McFarland et al, , 1993McFarland et al, , 1996Pentony et al, 2000;Todosijević, 2005;Todosijević & Enyedi, 2008;Van Hiel et al, 2006;Wronski et al, 2018). This evidence for LWA can be roughly grouped into two source types.…”
Section: Left-wing Authoritarianismmentioning
confidence: 99%
“…Historically, many researchers have argued for the possibility of left-wing authoritarianism (e.g., Eysenck, 1954;Mullen et al, 2003;Ray, 1983;Rokeach, 1960;Shils, 1954), and burgeoning evidence spanning multiple nations and three continents validates many of these conceptual arguments Conway & McFarland, 2019;Conway et al, in press;Costello et al, 2020a;Conway et al, 2020b;De Regt, Mortelmans, & Smits, 2011;Fasce & Avendaño, 2020;Federico et al, 2017;McFarland et al, 1992McFarland et al, , 1993McFarland et al, , 1996Pentony et al, 2000;Todosijević, 2005;Todosijević & Enyedi, 2008;Van Hiel et al, 2006;Wronski et al, 2018). This evidence for LWA can be roughly grouped into two source types.…”
Section: Left-wing Authoritarianismmentioning
confidence: 99%
“…This intriguing view captures a potential phenomenon that has been regarded as a "reactionary drift" within the left wing (Ovejero, 2018;Babones, 2018;Lukianoff & Haidt, 2018), which would be characterized by increasing abandon of public reason, open deliberation, and liberal values, preferring instead a rather paradoxical endorsement of illiberal identity politics (Strauts & Blanton, 2015;Clayton, 2018;Conway, Zubrod, Chan, McFarland, & Van de Vliert, 2021). This reactionary drift would be explicit in recent incidents in which left-wing activists, counting on political and institutional support, have exerted repressive actions of censorship (e.g., The Atlantic, 2015; The New York Times, 2017; CBC News, 2017;Inside Higher Ed, 2019), often exhibiting violent behaviors (e.g., CNN, 2017;Fox News, 2020)-also in the Spanish-speaking context (e.g., Clarín, 2017;El Mundo, 2019;La Vanguardia, 2019).…”
Section: Civil Liberties At the Crossroadsmentioning
confidence: 89%
“…Recent research has gathered evidence of authoritarian dispositions among leftwing voters in populations from the Spanish-speaking context (Fasce & Avendaño, 2020;Avendaño, Fasce, Costello, & Adrián-Ventura, 2021), Europe (Van Hiel, Duriez, & Kossowska, 2006;De Regt, Mortelmans, & Smits, 2011), the United States (Conway, Houck, Gornick, & Repke, 2017;Federico, Fisher, & Deason, 2017;Conway & McFarland, 2019), and worldwide (Conway, Zubrod, Chan, McFarland, & Van de Vliert, 2021), generally with lower prevalence than in the right-wing (Nilsson & Jost, 2020). Recent work by Costello, Bowes, Stevens, Waldman, and Lilienfeld (2021) suggest that left-wing authoritarianism is composed of three factors: Revolutionary aggression-a disposition to violently overthrow and punish the established figures of authority and power; top-down censorship-the motivation to exert group authority to regulate right-wing or deviant ideology and behaviors; and anti-conventionalism-a sense of moral superiority and absolutism, with a corresponding dismissal of conservatives as inherently immoral and a need for ideological homogeneity in one's environment.…”
Section: Second Hypothesis: Illiberal Attitudes Within Groups Of Leftistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the seminal work of Altemeyer (1981), authoritarianism had been conceptualized as an eminently right-wing construct reflecting an aggressive form of social conventionalism, based on the imposition of moral and social imperatives (Feldman, 2003). Nevertheless, the study of left-wing authoritarianism is gaining momentum (e.g., Conway, Houck, Gornick, & Repke, 2017;Fasce & Avendaño, 2020;Conway, Zubrod, Chan, McFarland, & Van de Vliert, 2021). In fact, Costello, Bowes, Stevens, Waldman, and Lilienfeld (2021) have advanced a domain-specific measurement of left-wing authoritarianism, which concluded that the construct is composed of three dimensions-all of them, in our view, potentially predicted by endorsement of leftist identity politics: 1) Revolutionary aggression: A disposition to violently overthrow and punish the established figures of authority or power.…”
Section: Left-wing Authoritarianism As a Political Manifestation Of Imentioning
confidence: 99%